MetaSort untangles metagenome assembly by reducing microbial community complexity - Peifeng Ji (Nature Portfolio, 2017)
Currently available metagenomic data analysis relies on reference genomes. Here, the authors describe a newde novometagenomic assembly method, metaSort, that constructs bacterial genomes from metagenomic samples to reduce microbial community complexity while increasing genome recovery and assembly.